2005
DOI: 10.1021/jm050018q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyamine Homologation on the Transport and Biological Properties of Heterocyclic Amidines

Abstract: Five sets of heterocyclic derivatives of various sizes and complexities coupled by an amidine function to putrescine, spermidine, or spermine were prepared. They were essentially tested to determine the influence of the polyamine chain on their cellular transport. To comment on affinity and on selective transport via the polyamine transport system (PTS), K(i) values for polyamine uptake were determined in L1210 cells, and the cytotoxicity and accumulation of the conjugates were determined in CHO and polyamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 91 publications
1
25
0
Order By: Relevance
“…Therefore, the elevated requirement of tumor cells for polyamines makes the polyamine pathway attractive for tumor targeted chemotherapy [2,3]. Recent data revealed that polyamines are potential vehicles to carry diverse cytotoxic drugs [4,5], this idea was on account of tumor cells could import both native and structurally modified polyamines from exogenous sources via the active polyamine transporter (PAT) which is up-regulated in many tumor cell lines [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the elevated requirement of tumor cells for polyamines makes the polyamine pathway attractive for tumor targeted chemotherapy [2,3]. Recent data revealed that polyamines are potential vehicles to carry diverse cytotoxic drugs [4,5], this idea was on account of tumor cells could import both native and structurally modified polyamines from exogenous sources via the active polyamine transporter (PAT) which is up-regulated in many tumor cell lines [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The active and passive transport systems of tumor cells have a greater capacity than those of normal cells. Tumor cells need this greater capacity to constantly supply the large quantity of nutrients needed to support their characteristic unabated growth [62][63][64] . Whereas the lack of effectivenes of DFMO as a chemotherapeutic agent seems to be due to its poor transport into the cells 11 , NCAO apparently utilizes the efficient transport capacity of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the PTS can readily take up heterocyclic derivatives if conjugated to natural polyamines. 38 Hence, recent studies in PDT have focused on comparing the efficacy of porphyin-polyamine conjugates in relation to Photofrin. These studies indicate a better efficiency of polyamine conjugates over the clinically approved PS.…”
Section: Porphyrin-polyamine Conjugatesmentioning
confidence: 99%
“…41,42 The results suggest that carboranylchlorins are good candidates for this dual treatment modality and warrant further investigations. Recently, seven polyamine conjugates of a tri(p-carboranylmethylthio)-tetrafluorophenylporphyrin (33)(34)(35)(36)(37)(38)(39) were prepared in high yields by sequential substitution of the p-phenyl fluoride of tetrakis(pentafluorophenyl)porphyrin (TPPF) (Fig. 9).…”
Section: Porphyrin-polyamine Conjugatesmentioning
confidence: 99%